Norms in Transition? The Relationship between Education and Singlehood - Diahhadi Setyonaluri; Aidah Maghfirah; Calvin Aryaputra (Jurnal Studi Pemuda, 2020)
This article examines the role of education in the likelihood of being never married among older adults in Indonesia. Following the Multiple Equilibrium Framework, our paper argues that increasing education imposes a more common trend of singlehood since marriage continues to be a near universal norm in Indonesia. Previous research found that increase in education delays marriage, but few studies have paid attention to the role of education in the decision to stay single. We use Indonesia National Socio-Economic Survey or SUSENAS 2007 and 2017 - two datasets with ten years span - to see whether there has been a change in the effect of education on the probability of permanent singlehood among women and men aged 40-65. The result from the logistic regression confirms a U-shaped relationship between education and singleness propensity. Our key finding is that an additional year of schooling reduces the probability of being single up until senior secondary level, while having education beyond high school increases the probability of being single. Our result implies that traditional norm towards gender role remains strong in Indonesia. We also find that both highly educated women and men have similar likelihood to stay single in this setting.